Pengaruh Kemampuan Kerja terhadap Kinerja Personel Satsamapta Polres Pamekasan yang Dimediasi oleh Pengembangan Karir - Chamariyah Chamariyah; Woro Utari; Dendi Apriliyanto Handika Putra (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Dendy Aprilianto Handika Pratama (2025). The Influence of Work Ability on the Performance of SATSAMAPTA Personnel at the Pamekasan Police Department. Postgraduate Program, Wijaya Putra University, Surabaya. Based on its approach, this research falls under the category of explanatory research. The research sample consisted of 80 respondents. The objectives of this research are as follows: To test and analyze the significant influence of work ability on the performance of SATSAMAPTA personnel at the Pamekasan Police Department. To test and analyze the significant influence of work ability on the career development of SATSAMAPTA personnel. To test and analyze the significant influence of career development on the performance of SATSAMAPTA personnel. To test and analyze the significant influence of work ability on the performance of SATSAMAPTA personnel as mediated by career development. The results of the study indicate that: Work ability has a significantly positive effect on the performance of SATSAMAPTA personnel at the Pamekasan Police Department, with an original sample value of 0.236. Work ability has a significantly positive effect on career development, with an original sample value of 0.483. Career development has a significantly positive effect on performance, with an original sample value of 0.432. Work ability has a significantly positive effect on performance mediated by career development, with an original sample value of 0.209.